2021
DOI: 10.3390/dairy2010008
|View full text |Cite
|
Sign up to set email alerts
|

Functional Odd- and Branched-Chain Fatty Acid in Sheep and Goat Milk and Cheeses

Abstract: The inverse association between the groups of odd-chain (OCFA) and branched-chain (BCFA) and the development of diseases in humans have generated interest in the scientific community. In experiment 1, the extent of the passage of odd- and branched-chain fatty acids (OBCFA) from milk fat to fresh cheese fat was studied in sheep and goats. Milk collected in two milk processing plants in west Sardinia (Italy) was sampled every 2 weeks during spring (March, April and May). In addition, a survey was carried out to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…When compared to the CTRL-fed goats, the CBS-fed goats ingested lower amounts of PUFA from the diet (Table 2). As PUFA are known to exert toxic effects on the rumen microflora, particularly on cellulolytic bacteria, a reduced PUFA intake from the diet may have determined a quantitative increase of bacteria biomass inside the rumen (82), and a subsequent higher availability of BCFA for milk fat synthesis in the mammary gland (83). In addition, the higher fiber content of the CBS diet (Table 1) may also partly explain the observed increase of BCFA in the CBS-fed goats, as a positive association has been previously reported between dietary fiber and FA of microbial origin (83).…”
Section: Milk Fatty Acid Profilementioning
confidence: 99%
“…When compared to the CTRL-fed goats, the CBS-fed goats ingested lower amounts of PUFA from the diet (Table 2). As PUFA are known to exert toxic effects on the rumen microflora, particularly on cellulolytic bacteria, a reduced PUFA intake from the diet may have determined a quantitative increase of bacteria biomass inside the rumen (82), and a subsequent higher availability of BCFA for milk fat synthesis in the mammary gland (83). In addition, the higher fiber content of the CBS diet (Table 1) may also partly explain the observed increase of BCFA in the CBS-fed goats, as a positive association has been previously reported between dietary fiber and FA of microbial origin (83).…”
Section: Milk Fatty Acid Profilementioning
confidence: 99%
“…Noteworthy FA in suckling lamb meat are the odd-chain FA (OCFA) and BCFA. These FA are considered biomarkers of rumen microbial fermentation and their amount in the meat of suckling lambs, which are still functional monogastric, is likely related to their concentration in the maternal milk [ 13 ]. The odd- and branched-chain fatty acids (OBCFA), not considered for a long time because of their low content in the total fat, have recently received increasing attention in human nutrition due to their potential health properties.…”
Section: The Quality Of Sucking Lamb Fatmentioning
confidence: 99%
“…A recent study demonstrated that C15:0 has a direct role in attenuating multiple comorbidities in humans as inflammation, anemia, and dyslipidemia [ 56 ]. Lamb meat, together with dairy foods, represents the main source of both OCFA and BCFA in the human diet [ 13 ].…”
Section: The Quality Of Sucking Lamb Fatmentioning
confidence: 99%
See 1 more Smart Citation
“…Seasonality of milk composition is characterized by periods of "peak" milk production, after which milk yield declines in summer, as animals go from the mid to late stages of their lactation, and this is more marked in extensive breeding systems, due to changes in the quality and availability of natural pasture. Seasonality of milk fatty acid (FA) composition was studied by Nudda et al [4], which turned their attention from the amply studied health beneficial omega-3 FA and conjugated linoleic acid (CLA) to the odd and branched chain classes of FA. The latter, long neglected, have recently sparked interest in the scientific community due to an inverse relationship with the development of human diseases.…”
mentioning
confidence: 99%